Association of Maternal SARS-CoV-2 Infection in Pregnancy With Neonatal Outcomes. Issue 1 (March 2022) - Norman, M.; Navér, L.; Söderling, J.; Ahlberg, M.; Hervius Askling, H.; Aronsson, B.; Byström, E.; Jonsson, J.; Sengpiel, .; Ludvigsson, J.F.; Håkansson, S.; Stephansson, O.
Abstract : ( JAMA . 2021;325:2076–2086. doi: 10.1001/jama.2021.5775) There has been uncertainty regarding the effects of SARS-CoV-2 on neonates since the beginning of the COVID-19 worldwide pandemic, which has led to varying infant management recommendations. A balance needs to be found between interfering with the mother-infant interactions following birth and protecting the infants from SARS-CoV-2 and any adverse effects. The aim of this study was to identify associations between maternal SARS-CoV-2 positivity and adverse neonatal outcomes.